Videogames: escapism or an effective tool for anticorruption enlightenment? - A. L. Melnikova; A. S. Mitsul (Russian Journal of Economics and Law)
Objective: to analyze video games with anticorruption components and to make a conclusion of the possibility to use them in anticorruption education with various mechanics, plots and narratives.Methods: analysis and summarization of the narrative of commercial video games, studies of the scientific literature and research aimed at revealing the influence of video games on a player’s cognitive abilities, as well as studying the possibilities of using video games in education and enlightenment allowed us to assume that video games may be used as an auxiliary instrument for anticorruption enlightenment.Also, we analyzed the audience of video games players to determine its relevancy for the goals of anticorruption education. According to the goals of anticorruption education identified by us, namely: ability to distinguish corruption and its types, developing negative attitude to corruption and positive attitude to a whistle-blower, illustration of short-term and long-term consequences of corruption – we performed a critical analysis of the video games narrative in order to identify the ones most appropriate for anticorruption education.Results: in the work, we studied the educational potential of video games and determined the efficiency level of their influence of the educational process. By the example of particular game projects, we proved in practice the expediency of using video games as a tool of anticorruption education.Scientific novelty: the article proves inexpediency of assessing video games exclusively as a form of escapism and, for the first time, specifies the examples of practical implementation of commercial video games, not being training programs or simulators, for organization of anticorruption education.Practical significance: the main conclusions of the article can be used in practical activity when developing long-term strategies and programs of anticorruption education, as well as within the activity of developing video games to assess longterm consequences of the narrative used.